PANDANGAN HUKUM ATAS ANCAMAN DEBT COLLECTOR PINJAMAN ONLINE YANG AKAN MENYEBARLUASKAN DATA PRIBADI - Madjid, Abdul Gani (LPPM Universitas Doktor Husni Ingratubun Papua, 2025)
The rise of online loan services (pinjol) in the digital era provides easy access to finance for the community. However, this phenomenon is accompanied by the practice of personal data abuse by debt collectors, who often threaten to disseminate borrower data as a form of intimidation. This action not only violates the privacy rights of citizens, but also contradicts the legal principles of personal data protection. This research aims to analyze the actions of debt collectors in the perspective of Indonesian law, especially in the context of the Personal Data Protection Law (Law No. 27 of 2022) and the Criminal Code. The research method used is normative juridical with a statutory, case study, and conceptual approach. The results show that the threat of spreading personal data is a criminal offense and violates the borrower's right to privacy. Criminal and administrative sanctions can be imposed on the perpetrators, but weak law enforcement is still a major challenge. Therefore, it is necessary to strengthen supervision by OJK, public education, and stricter law enforcement against violations by debt collectors.